2017
DOI: 10.14710/jitaa.42.1.6-13
|View full text |Cite
|
Sign up to set email alerts
|

The effect of liquid tumeric extract supplementation on carcass production and chemical quality of broiler meat

Abstract: ABSTRAKTujuan penelitian ini adalah untuk mengetahui efek penambahan ekstrak kunyit sediaan cair (EKC) sebagai fitobiotik terhadap produksi karkas dan kualitas kimia daging ayam broiler. Penelitian dilakukan dengan rancangan percobaan acak lengkap pola searah. Ayam broiler 84 ekor dipelihara sejak usia 0 hingga 42 hari. Umur 0-14 hari diberi pakan komersial (ME: 3100 kcal/kg; CP 22%; Ca 1%; P 0,75%). Umur 15-21 hari diberi pakan campuran komersial dan basal (ME 3201,77 kcal/kg; CP 20,21%; Ca 0,90%; P 0,43%). U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…A previous study report that the addition of 0.5% TF significantly (p<0.01) reduces blood fat levels [16,39], abdominal fat, and liver percentages [40]. This is because curcumin has hypolipidemic and hypocholesterolemic properties that can decrease fat levels of broiler meat [41], stimulate bile secretion, and bile flow that can support liver health[38] and abdominal fat has a positive correlation with carcass weight and the percentage of abdominal fat in broilers reaches 2-3.13% at 4-8 weeks of slaughter period [11].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study report that the addition of 0.5% TF significantly (p<0.01) reduces blood fat levels [16,39], abdominal fat, and liver percentages [40]. This is because curcumin has hypolipidemic and hypocholesterolemic properties that can decrease fat levels of broiler meat [41], stimulate bile secretion, and bile flow that can support liver health[38] and abdominal fat has a positive correlation with carcass weight and the percentage of abdominal fat in broilers reaches 2-3.13% at 4-8 weeks of slaughter period [11].…”
Section: Resultsmentioning
confidence: 99%
“…Yet, inconsistent findings were reported. Hidayat et al [17] did not see any effect of turmeric extract on carcase and meat quality of broilers. Also, Singh et al [18] reported no influence of black pepper powder on carcase characteristics and abdominal fat content of broilers.…”
Section: Introductionmentioning
confidence: 89%
“…Similarly, Ibrahim et al (2021) included cornelian cherry extract in 50, 100, 200, and 400 mg/kg diets, and found no effect on crude protein and crude fat of breast and thigh meats broilers. Also, Hidayat et al (2017) administrated liquid turmeric extract at 2, 4, 6, 8, and 10% in drinking water. At the levels of 8 and 10%, treatment reduced the water content of broiler meats.…”
Section: Effect Of Plant-derived Products On Chemical Compositions Of...mentioning
confidence: 99%